Transforming Waste into Blessings: The Role of Environmental Literacy at SDN Warnasari Cilegon in Promoting a Recycling Culture and Waste Management in Elementary Schools - Uyun, Hairul; Supriatna, Nana; Supriatna, Encep (Papanda Publisher, 2025)
Environmental literacy programs in industrial contexts remain underexplored despite growing recognition of their importance in addressing local environmental challenges. This study examined the effectiveness of an environmental literacy program at SDN Warnasari Cilegon in enhancing students' environmental knowledge, attitudes, and behaviors within an industrial city setting. A descriptive quantitative pre-post intervention design was employed with 180 elementary students (grades IV-VI) who participated in a contextually relevant environmental literacy program focusing on waste management and water conservation. Data collection utilized validated questionnaires, behavioral observations, and semi-structured interviews. Pre-post comparisons were analyzed using paired-samples t-tests with effect sizes calculated using Cohen's d. Results demonstrated significant improvements across all dimensions: environmental knowledge increased from 58.4 to 78.6 points (p < 0.001, d = 1.67), attitudes improved from 3.12 to 4.21 on a five-point scale (p < 0.001, d = 1.72), and behaviors showed substantial enhancement with participation rates increasing by 40-55% in key environmental practices. Qualitative findings revealed that hands-on, locally relevant activities were particularly effective in connecting theoretical knowledge to practical application. The program successfully addressed the knowledge-behavior gap through experiential learning approaches targeting industrial city-specific environmental challenges. This research contributes novel insights into environmental literacy program effectiveness in industrial contexts, providing a replicable model for educational institutions facing similar environmental pressures and demonstrating the critical importance of contextual relevance in environmental education programming.